CONTRIBUTION TO THE KNOWLEDGE OF THE VASCULAR FLORAOF NORTHERN BOSNIA (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Floristic research in the northern Bosnia confirmed a high level of plant biodiversity (78 families, 227 genera, 358 species and subspecies of Pteridophyta and Spermatophyta). The most represented species are from families Compositae (15,4%), Lamiaceae (8%), Fabaceae (6,5%) and Rosaceae (6,5%). Registered stenoendemic (3) and subendemic species (4) gives a special feature to the researched area. Endargened plant species, identified in the researched area, are found in the Bosnian (25) and European Red List of Threatened species (184), which is the best indicator of the conservation state of natural habitats and species in the northern Bosnia. The analysis of the used value of registered plant taxa showed that the area of northern Bosnia has quality and sufficient natural resources in terms of medicinal, vitamin, edible, aromatic and honey species (Rosaceae, Compositae, Lamiaceae, Apiaceae, Fabaceae etc.).